2021
DOI: 10.1016/j.ajem.2020.09.086
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of increasing COVID-19 in health care workers after implementation of high flow nasal cannula: A safety evaluation

Abstract: Background Initial recommendations discouraged high flow nasal cannula (HFNC) in COVID-19 patients, driven by concern for healthcare worker (HCW) exposure. Noting high morbidity and mortality from early invasive mechanical ventilation, we implemented a COVID-19 respiratory protocol employing HFNC in severe COVID-19 and HCW exposed to COVID-19 patients on HFNC wore N95/KN95 masks. Utilization of HFNC increased significantly but questions remained regarding HCW infection rate. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…Early in the COVID-19 pandemic, infection control concerns surrounding use of HFNC led many to favor endotracheal intubation in order to limit potential aerosol generation and dispersion. Evaluation of past and emerging data coupled with hard-won clinical experience have dispelled many of these concerns [ 103 , 104 ]. In one healthcare system, implementation of a respiratory protocol increasing the use of HFNC in a dedicated COVID-19 intermediate care unit with non-negative pressure rooms did not result in any significant increase in symptomatic COVID-19 infections among staff compared to those working in COVID-19 units not using HFNC [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early in the COVID-19 pandemic, infection control concerns surrounding use of HFNC led many to favor endotracheal intubation in order to limit potential aerosol generation and dispersion. Evaluation of past and emerging data coupled with hard-won clinical experience have dispelled many of these concerns [ 103 , 104 ]. In one healthcare system, implementation of a respiratory protocol increasing the use of HFNC in a dedicated COVID-19 intermediate care unit with non-negative pressure rooms did not result in any significant increase in symptomatic COVID-19 infections among staff compared to those working in COVID-19 units not using HFNC [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] However, multiple studies generated a cumulative low-moderate quality of evidence, which indicate a relatively low risk of dispersing a significant amount of bio-aerosol particles and suggest no increase in the risk of infection transmission to healthcare workers with an excellent fitted HFNC, good sealing circuit, and appropriate adherence to airborne precautions. [ 26 25 24 25 26 27 28 29 30 31 ] Yet, high-quality evidence on the risk of airborne contamination and nosocomial infection with the use of HFNC for the management of COVID-19 patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…During a cough-simulating scenario, HFNO moderately increased the distance of droplet dispersion by an average of 0.42 m [ 74 ]. On the other hand, other investigators demonstrated that there was no significant difference in the risk of aerosol production and dispersion between spontaneous breathing, conventional oxygen treatment and HFNO or NIV therapy [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ], and that these modalities do not expose healthcare workers to higher infection risk provided that they follow the appropriate personal protection precautions [ 82 , 83 , 84 ]. In a very interesting recent article by Gaeckle and coworkers, aerosol generation from healthy participants receiving oxygen via a non-humidified nasal cannula, face mask, HFNO and NIV was measured during normal breathing, talking, deep breathing and coughing [ 75 ].…”
Section: Risks Of Noninvasive Respiratory Treatments In Severe Covid-19mentioning
confidence: 99%